2021
DOI: 10.3389/fphys.2021.784391
|View full text |Cite
|
Sign up to set email alerts
|

The Insulin-Sensitizer Pioglitazone Remodels Adipose Tissue Phospholipids in Humans

Abstract: The insulin-sensitizer pioglitazone exerts its cardiometabolic benefits in type 2 diabetes (T2D) through a redistribution of body fat, from ectopic and visceral areas to subcutaneous adipose depots. Whereas excessive weight gain and lipid storage in obesity promotes insulin resistance and chronic inflammation, the expansion of subcutaneous adipose by pioglitazone is associated with a reversal of these immunometabolic deficits. The precise events driving this beneficial remodeling of adipose tissue with pioglit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 67 publications
0
16
0
2
Order By: Relevance
“…5H ) in HFD mice. Furthermore, even though TAGs and DAGs make up a significant portion of total lipids in other tissues (e.g., adipose tissue [54] or liver [55]), these lipids were generally not as abundant in pancreatic islets ( Fig. 5A ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…5H ) in HFD mice. Furthermore, even though TAGs and DAGs make up a significant portion of total lipids in other tissues (e.g., adipose tissue [54] or liver [55]), these lipids were generally not as abundant in pancreatic islets ( Fig. 5A ).…”
Section: Resultsmentioning
confidence: 99%
“…6A – 6D ). Phosphatidylserine (PS), an inner phospholipid that is externalized in states of metabolic stress and apoptosis [56], and phosphatidic acid (PA), the obligate precursor for all glycerophospholipids [54], tended to decrease in HFD-feeding conditions in terms of absolute ( Fig. 5F ) and relative abundance ( Supp.…”
Section: Resultsmentioning
confidence: 99%
“…This specialized tissue is a connective tissue consisting of specialized cells called adipocytes and other types of cells. The health of AT is critical in terms of metabolic disorders, as it plays essential metabolic roles as will be discussed in Section 2 [ 9 ]. Dysfunctional AT can cause different pathologies and metabolic diseases, including IR and cardiovascular disorders (CVDs).…”
Section: Introductionmentioning
confidence: 99%
“…Adipose tissue of obese type 2 diabetic humans treated with pioglitazone was the focus of another study. Findings demonstrated that pioglitazone protects the immunometabolic health of adipocytes through selective remodeling of the glycerophospholipid pool, characterized by a decrease in lipids enriched for arachidonic acid, such as plasmanylethanolamines and phosphatidylinositols ( Palavicini et al, 2021 ). At the other end of the species’ spectrum, studies examined molecular mechanisms mediating food-induced reinforcement in the model system C. elegans .…”
Section: Grand Challenge: Organ Regulation In Metabolic Physiologymentioning
confidence: 99%